2022
DOI: 10.17275/per.22.57.9.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Immersive Virtual Reality Environments on Students' Academic Achievement: A Meta-analytical and Meta-thematic Study

Abstract: The objective of this study is to ascertain the effects of immersive virtual reality environments on students' academic achievement utilizing quantitative and qualitative approaches. First, databases of Web of Science, Google Scholar, ERIC, Proquest, YÖK Thesis Center, and ULAKBİM of Turkey were searched, and 31 studies (23 journal papers and 8 theses) were selected for the meta-analysis. In this context, the overall effect size on students' academic achievement was analyzed with the CMA program using subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…Learning Environment in Education: An Overview [24] critically examined the immersive virtual reality-based environments as a predictor of student's academic achievement by applying metaanalysis and meta-thematic approach. The content analysis and meta-analysis of the research studies revealed that ILEs have wide educational effects like providing learning autonomy, increasing attention, providing permanent learning, self-regulated learning, active participation, increasing comprehension of lesson, providing in-depth learning etc.…”
Section: Critical Analysis Of Immersivementioning
confidence: 99%
See 2 more Smart Citations
“…Learning Environment in Education: An Overview [24] critically examined the immersive virtual reality-based environments as a predictor of student's academic achievement by applying metaanalysis and meta-thematic approach. The content analysis and meta-analysis of the research studies revealed that ILEs have wide educational effects like providing learning autonomy, increasing attention, providing permanent learning, self-regulated learning, active participation, increasing comprehension of lesson, providing in-depth learning etc.…”
Section: Critical Analysis Of Immersivementioning
confidence: 99%
“…Akgun & Atici [24] conducted a meta-analytical and meta-thematic study to gain understanding regarding the effectiveness of immersive virtual reality environments in terms of academic performance of learners by following a mixed design. The study revealed a moderate positive effect of ILEs on student's academic success, and along with these, the meta-thematic analysis revealed significant effects in cognitive, affective and psychomotor skills of the students and several academic benefits.…”
Section: Effectiveness Of Immersive Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation